2019
DOI: 10.3389/fphar.2019.01249
|View full text |Cite
|
Sign up to set email alerts
|

Embelin Protects Against Acute Pentylenetetrazole-Induced Seizures and Positively Modulates Cognitive Function in Adult Zebrafish

Abstract: Purpose of the research: Epilepsy is a continuous process of neurodegeneration categorized by an enduring tendency to generate uncontrolled electrical firing known as seizures causing involuntary movement all over the body. Cognitive impairment and behavioral disturbances are among the more alarming co-morbidities of epilepsy. Anti-epileptic drugs (AEDs) were found to be successful in controlling epilepsy but are reported to worsen cognitive status in patients. Embelin (EMB) is a benzoquinone derived from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 76 publications
(93 reference statements)
5
14
1
Order By: Relevance
“…The reduced inflection ratio in the second hit PTZ group at 3 and 24 h when compared to the VC group reflect the memory impairment in the second hit PTZ group. This finding is in agreement with earlier finding reporting PTZ induced cognitive impairment in adult zebrafish ( Kundap et al, 2019a ). These impairment in memory induced by second hit PTZ was ameliorated upon treatment with mAbs as evidenced by increased inflection ratio at 3 h and 24 h. Worth mentioning here is that, the significant upregulation of inflection ratio was only observed with mAb 5 at 24 h T-maze test.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The reduced inflection ratio in the second hit PTZ group at 3 and 24 h when compared to the VC group reflect the memory impairment in the second hit PTZ group. This finding is in agreement with earlier finding reporting PTZ induced cognitive impairment in adult zebrafish ( Kundap et al, 2019a ). These impairment in memory induced by second hit PTZ was ameliorated upon treatment with mAbs as evidenced by increased inflection ratio at 3 h and 24 h. Worth mentioning here is that, the significant upregulation of inflection ratio was only observed with mAb 5 at 24 h T-maze test.…”
Section: Discussionsupporting
confidence: 94%
“…Several lines of investigation have earlier reported that epileptic zebrafish exhibited memory impairment ( Kundap et al, 2017 ; Kundap et al, 2019a ) which is in agreement with the fact that memory impairment is associated with epilepsy ( Kesselmayer et al, 2019 ; Laurent et al, 2020 ). This reflects that the future therapeutic strategies against epileptic seizures should not only exert the disease supression but also ameliorate the related memory impairment.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…76−78 Reduced level of NPY in our second hit PTZ group depicts the occurrence of seizure and impairment in learning and memory, which corroborates the reduced mRNA expression of NPY in PTZ and second hit PTZ induced seizure in adult zebrafish. 79,80 However, pretreatment with GL 25, GL 50, and GL 100 does not exert any significant effect in modulating the mRNA expression of NPY when compared to the second hit PTZ group.…”
Section: Resultsmentioning
confidence: 87%